Combination Analysis of Metatranscriptome and Metagenome Reveal the Composition and Functional Response of Coral Symbionts to Bleaching During an El Niño Event - Sun, Fulin; Yang, Hongqiang; Wang, Guan; Shi, Qi (Frontiers in Microbiology, 2020)
With the abnormal rise in ocean temperatures globally in recent years, coral bleaching is becoming common and serious. However, the response mechanisms and processes of coral symbionts to bleaching are not well understood. In this study, metagenomics and metatranscriptomics were used to explore the composition of coral symbionts and their functions in response to coral bleaching. All four bleaching coral species displayed a significant reduction of the abundance and function of Dinophyceae-like eukaryotes at the DNA and RNA levels. However, different species of bleaching coral have their own characteristic symbiotic components. Bleaching Acropora tenuis and Goniastrea minuta corals exhibited a very high abundance of prokaryotes and associated gene functions, especially for opportunistic bacteria. In contrast algae and fungi were identified as the main microbial associate components and had relatively high RNA abundance in bleaching Pocillopora verrucosa and Pocillopora meandrina. Different coral species, whether unbleached or bleaching, have the same symbiotic taxa that perform the same biological functions in vivo. Different stages of bleaching, or transitional states, were identified by different genome content and functional gene abundance among bleaching corals. These stages should be considered in future coral bleaching studies to accurately determine symbiont structure and function. An implicit hypothesis is that there is a causal relationship between the stability of eukaryotic communities and coral bleaching.